A Brief Self‐Affirmation Study to Improve the Experience of Minority Patients. Issue 2 (4th October 2013) - Burgess, Diana J.; Taylor, Brent C.; Phelan, Sean; Spoont, Michele; van Ryn, Michelle; Hausmann, Leslie R.M.; Do, Tam; Gordon, Howard S.
<x xml:space="preserve">Abstract</x> Background: There is evidence that Black patients may experience stereotype threat—apprehension about being negatively stereotyped—in healthcare settings, which might adversely affect their behavior in clinical encounters. Recent studies conducted outside of healthcare have shown that a brief self‐affirmation intervention, in which individuals are asked to focus on and affirm their valued characteristics and sources of personal pride, can reduce the negative effects of stereotype threat on academic performance and on interpersonal communication. Methods: This randomised controlled trial examined whether a self‐affirmation (SA) intervention would decrease the negative effects of stereotype threat (negative mood, lower state self‐esteem, greater perceptions of racial discrimination) and increase communication self‐efficacy among Black primary care patients. Self‐affirmation was induced by having patients complete a 32‐item values affirmation questionnaire. Results: Patients in the SA condition had lower levels of performance self‐esteem and social self‐esteem than patients in the control. There were no differences between the SA and the control groups on negative mood, communication self‐efficacy, and perceptions of discrimination. Conclusions: Our SA intervention lowered state self‐esteem among Black patients. Future research is needed to determine the type of SA task that is most effective for this population.